Saints versus sinners. Does morality matter? - Durand, Robert B; Koh, Sze; Limkriangkrai, Manapon (Elsevier BV North-Holland, 2013)
Social norms constrain investors from investing in “sin stocks”, affecting the returns and corporate financial policies of such firms (Hong and Kacperczyk, 2009). This paper finds that “Saints” are influenced by social norms. In almost all instances, where an effect on “Sinners” is positive (negative), we find that the effect for ‘Saints’ is negative (positive). Hong and Kacperczyk provide evidence that social norms prevent ‘evil’ outcomes. This paper finds that social norms exert positive pressure on both investors and firms in the US equity market.